Robot Morality: Bertram F. Malle’s Concept of Moral Competence - Schmiljun, André (ETHICS IN PROGRESS, 2018)
Bertram F. Malle is one of the first scientists, combining robotics with moral competence. His theory outlines that moral competence can be understood as a system of five components including moral norms, a moral vocabulary, moral cognition, moral decision making and moral communication. Giving a brief (1) introduction of robot morality, the essay analyses Malle’s concept of moral competence (2) and discusses its consequences (3) for the future of robot science. The thesis will further argue that Malle’s approach is insufficient due to three reasons: his function argument is very simplifying and therefore troubling; each component of his theory is inconsistent and, finally, closely connected to our common understanding of personhood, which raises new philosophical questions surrounding the basic issue of if and/or when machines can be considered people.